Post-transcriptional regulation of SHANK3 expression by microRNAs related to multiple neuropsychiatric disorders. Issue 1 (December 2015) - Choi, Su-Yeon; Pang, Kaifang; Kim, Joo; Ryu, Jae; Kang, Hyojin; Liu, Zhandong; Kim, Won-Ki; Sun, Woong; Kim, Hyun; Han, Kihoon
Abstract Background Proper neuronal function requires tight control of gene dosage, and failure of this process underlies the pathogenesis of multiple neuropsychiatric disorders. TheSHANK3 gene encoding core scaffolding proteins at glutamatergic postsynapse is a typical dosage-sensitive gene, both deletions and duplications of which are associated with Phelan-McDermid syndrome, autism spectrum disorders, bipolar disorder, intellectual disability, or schizophrenia. However, the regulatory mechanism ofSHANK3 expression in neurons itself is poorly understood. Results Here we show post-transcriptional regulation ofSHANK3 expression by three microRNAs (miRNAs), miR-7, miR-34a, and miR-504. Notably, the expression profiles of these miRNAs were previously shown to be altered in some neuropsychiatric disorders which are also associated withSHANK3 dosage changes. These miRNAs regulated the expression ofSHANK3 and other genes encoding actin-related proteins that interact with Shank3, through direct binding sites in the 3′ untranslated region (UTR). Moreover, overexpression or inhibition of miR-7 and miR-504 affected the dendritic spines of the cultured hippocampal neurons in a Shank3-dependent manner. We further characterized miR-504 as it showed the most significant effect on bothSHANK3 expression and dendritic spines among the three miRNAs. Lentivirus-mediated overexpression of miR-504, which mimics its reported expression change in postmortem brain tissues of bipolar disorder, decreased endogenous Shank3 protein in cultured hippocampal neurons. We also revealed that miR-504 is expressed in the cortical and hippocampal regions of human and mouse brains. Conclusions Our study provides new insight into the miRNA-mediated regulation ofSHANK3 expression, and its potential implication in multiple neuropsychiatric disorders associated with alteredSHANK3 and miRNA expression profiles.